God the Father at the Table: The Centrality of the Overseer in the Letters of Ignatius of Antioch (Revista Archai, 2020)
The development of a kind of authority concentrated in one person is surely one of the main social processes in the first two centuries CE Christianity and also one of those which left the most perennial and influent legacies in the Christian Church of posterior centuries. In this sense, Ignatius of Antioch is not only an historical witness of the dynamics around such a process in Proconsular Asia of his time. He is also, and most of all, an historical agent who, using his rhetorical abilities and imprisonment conditions, works for the reorganization of the Christian communities around the one he defended to be the representation in the holy supper of God the Father himself.